Macrotroponins cause discrepancy in high-sensitivity examination - Broz, Pavel; Racek, Jaroslav; Prokop, Pavel; Novak, Jaroslav; Rajdl, Daniel; Trefil, Ladislav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
AIM: We present two cases with clearly discrepant results of clinical examination and cardiac troponin I (cTnI) and cardiac troponin T (cTnT) concentrations. In similar cases with discrepant results, the possibility of interference should be considered. METHODS: Due to the suspicion of the presence of macrotroponin I in both of the presented cases, the patients were invited to our laboratory and both cTnI (Architect i1000, Abbott) and cTnT (Cobas 8000, Roche) concentrations were analysed. The samples were treated by preincubation in a heterophilic antibodies blocking tube (HBT) and analysed. Precipitation with polyethylene glycol solution (PEG) and molecular weight separation by gel filtration on Sephadex G100 was performed and concentrations of cTnI were analysed. RESULTS: In the same blood sample, the cTnT and cTnI concentrations were 7 and 1782 ng/L, respectively, in Case 1, and 6 and 96 ng/L, respectively, in Case 2. Incubation of samples in HBT had no significant effect. CTnI concentrations after precipitation with PEG - presented as the percentage of initial concentrations - were 7.4% in Case 1 (and 26.8% in the control sample) and 1.4% in Case 2 (and 56.0% in the control sample). These results indicate a significant decrease in both cases, supporting presence of macrotroponin I. Finally, analyses of cTnI concentrations after gel filtration also supported the presence of macrotroponin I. CONCLUSION: The present cases show that the presence of macrotroponin can lead to unnecessary investigation of the patient. When the possibility of interference is suspected, cooperation with laboratory staff to help with interpretation or to perform more detailed analysis is crucial.
Keywords: Male; biologické markery; Biomarkers; macrotroponin; Troponin T; Aged; immunoassay; mužské pohlaví; senioři; troponin T; troponin I; lidé; ženské pohlaví; cardiac troponin; Humans; Troponin I; Female; lidé středního věku; interference; Middle Aged